Biomolecular modifications during keratinocyte differentiation: Raman spectroscopy and chromatographic techniques. Issue 9 (24th March 2021) - Bakar, Joudi; Michael-Jubeli, Rime; Tfaili, Sana; Assi, Ali; Baillet-Guffroy, Arlette; Tfayli, Ali
Abstract : From the basal layer until the stratum corneum, lipid and protein biomarkers associated with morphological changes denote keratinocyte differentiation and characterize each epidermis layer. Abstract : From the basal layer until the stratum corneum, lipid and protein biomarkers associated with morphological changes denote keratinocyte differentiation and characterize each epidermis layer. Herein, we followed keratinocyte differentiation in the early stages using HaCaT cells over a period of two weeks by two complementary analytical techniques: Raman microspectroscopy and high-performance liquid chromatography coupled with high resolution mass spectrometry. A high concentration of calcium in the medium induced HaCaT cell differentiation in vitro . The results from both techniques underlined the keratinocyte passage from the granular layer (day 9) to the stratum corneum layer (day 13). After 13 days of differentiation, we observed a strong increase in the lipid content, decrease in proteins, decrease in DNA, and a decrease in glucosylceramides/ceramides and sphingomyelins/ceramides ratios.